Wide-ranging radar simulation data generation method based on multi-scale electronic charts in a maritime simulator. Issue 2 (3rd May 2016) - Zhang, X.-Y.; Yao, S.; Bucknall, Richard; Liu, Y.-C.
ABSTRACT: In maritime simulators there are problems of discontinuity and saltation on radar simulation images caused by the limited range of radar simulation data generated from a single electronic chart. Furthermore, this kind of radar simulation is overlapping, discontinuous and redundant, and thus could lead to simulation error and training interruption. To address this problem, a method is presented to generate a wide range of radar simulation data based on a multi-scale chart data. The method uses automatic splicing on same-scale maps and variable-scale visualisation splicing on multi-scale maps. In this paper, the S-57 standard electronic navigational charts are filtered from the S-57 database and then radar simulation data are generated based on charts of different scales. From clipping, sorting, deletion, combination and matching, a wide range of continuous radar simulation data are generated. Taking the waters around Ningbo Port, China as an example, 27 chart sections are filtered out from S-57 database, with a longitude range from 121°33' to 122°56.8' and a latitude range from 29°3' to 30°21.8'. The wide-range and continuous radar simulation data are generated for a maritime simulator. The results validate this method as being highly accurate and able to meet the practical needs of maritime simulation.